DEVELOPMENT MECHANISMS OF THE MORAL CULTURE OF YOUTH ON THE BASE OF NATIONAL AND UNIVERSAL VALUES - Khotam Sirozhiddinov (Academia Science Repository, 2023)
The main condition for the existence and viability of a particular cultural group depends on the stability of the content of historically established moral norms. As a result of the development of the moral culture of young people on the basis of national and universal values, their viability increases. However, depending on the development of society, its economic, political and religious characteristics, a change in moral norms is inevitable.